Tinjauan Hukum Mengenai Sanksi Keperdataan Bagi Pelaku Pembuangan (Dumping) Sampah Limbah Medis Sembarangan - Muhammad Fikri Aufa; Riana Kesuma Ayu; Ma'rifah, Ma'rifah; Utami, Mieke Aprilia (CV. Strata Persada Academia, 2024)
Medical waste management is the responsibility of individuals or organizations involved in activities that generate medical waste. Proper and systematic management is required for medical waste classified as B3 waste, encompassing all stages from processing to disposal. This research aims to investigate and evaluate the implementation of legal penalties for those who negligently dispose of medical waste. This study methodology employs normative legal research, utilizing primary legal sources derived from statute rules and secondary data obtained from library resources. This research employs both a legislative and conceptual approach, utilizing a perspective analysis method. Improper disposal of medical waste can harm the environment and may result in legal penalties. This sanction can be imposed by both judicial and extrajudicial dispute settlement processes. The judges' decision towards the defendant must be carried out as a civil penalty agreed upon by the defendant, and a request for enforcement can be made.